General parallel computations on desktop grid and P2P systems - Browne, James C.; Yalamanchi, Madulika; Kane, Kevin; Sankaralingam, Karthikeyan (LCR '04: Proceedings of the 7th workshop on Workshop on languages, compilers, and run-time support for scalable systems, 2004)
This paper defines the requirements for effective execution of iterative computations requiring communication on a desktop grid. It then proposes a combination of a p2p communication model, an algorithmic approach (asynchronous iterations) and a programming model which has promise for satisfying those requirements. Experimental results from an implementation of asynchronous algorithms in pure p2p system will be given. The integration of the p2p communication model with a commercially supported implementation of the SETI@Home desktop grid system to yield a prototype implementation of a desktop grid with communication among its hosts is described and some very preliminary results from application of the extended desktop grid for computation of Google pageranks and solution of linear systems are given. The desktop grid prototype preserves anonymity among desktop hosts, supports dynamic communication set membership and enables transparent replication of computations for fault tolerance.